On the role of the tricarboxylic acid cycle in plant productivity - Zhang, Youjun; Fernie, Alisdair R. (Journal of integrative plant biology, 2018)
The tricarboxylic acid (TCA) cycle is one of the canonical energy pathways of living systems, as well as being an example of a pathway in which dynamic enzyme assemblies, or metabolons, are well characterized. The role of the enzymes have been the subject of saturated transgenesis approaches, whereby the expression of the constituent enzymes were reduced or knocked out in order to ascertain their in vivo function. Some of the resultant plants exhibited improved photosynthesis and plant growth, under controlled greenhouse conditions. In addition, overexpression of the endogenous genes, or heterologous forms of a number of the enzymes, has been carried out in tomato fruit and the roots of a range of species, and in some instances improvement in fruit yield and postharvest properties and plant performance, under nutrient limitation, have been reported, respectively. Given a number of variants, in nature, we discuss possible synthetic approaches involving introducing these variants, or at least a subset of them, into plants. We additionally discuss the likely consequences of introducing synthetic metabolons, wherein certain pairs of reactions are artificially permanently assembled into plants, and speculate as to future strategies to further improve plant productivity by manipulation of the core metabolic pathway. The tricarboxylic acid (TCA) cycle is one of the canonical energy pathways of living systems as well as being an example of a pathway in which dynamic enzyme assemblies or metabolons are well characterized. Given that a number of its variants in nature, here we discuss possible synthetic approaches involving introducing these variants, or at least a subset of them, into plants.